VIRTUAL REALITY (VR) AS AN EDUCATIONAL MEDIA TO PREVENT EARLY MARRIAGE AMONG ADOLESCENTS - Dessya Putri Ayu; Miftahul Jannah; Surya Dewi Puspita; Yohan Yuanta; Putri Rahayu Ratri (RADJA PUBLIKA, 2025)
Early marriage remains a significant social issue affecting adolescent health, education, and well-being, particularly in Karangpring Village, Sukorambi District, Jember. This study aimed to develop and evaluate the effectiveness of Virtual Reality (VR) as an educational medium for preventing early marriage among adolescents. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). During the analysis phase, a survey involving 30 adolescents was conducted to identify educational needs. The VR media titled “My Future in My Hands” was developed using Unity 3D and validated by three experts, yielding a 89,75% feasibility score (very feasible). Field implementation further showed a statistically significant improvement in adolescents’ knowledge scores after exposure to the VR simulation, underscoring its effectiveness as a learning tool. High user satisfaction ratings also reflected the acceptability and appeal of VR as a learning medium for digital-native youth. The findings demonstrate that VR is an effective and innovative educational tool to enhance adolescents’ awareness of early marriage risks. This approach can be integrated into community-based reproductive health education programs for youth.